1993
DOI: 10.1093/oxfordjournals.humrep.a138008
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy: Combined intra-uterine and extra-uterine pregnancy in the contralateral tube after gamete intra-Fallopian transfer

Abstract: A case of combined intra-uterine and contralateral tubal pregnancy after gamete intra-Fallopian transfer (GIFT) is presented. Laparotomy with partial tubal resection was performed after tubal rupture. The intra-uterine pregnancy is still ongoing without complications. Heterotopic pregnancies are dangerous conditions for the patient and should be taken into account after transfer of multiple oocytes. To our knowledge this is the first report of a heterotopic pregnancy in the contralateral tube after GIFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Moreover, Gamberdella and Marrs suggested that GIFT may increase the incidence of heterotopic pregnancy because multiple gametes are placed into fallopian tubes that may have microscopic endosalpingeal changes, which could result in multiple fertilization with the potential for both intrauterine and tubal implantation 23 . Interestingly, contralateral pregnancies after GIFT have been reported 24,25 . Ranieri et al 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Gamberdella and Marrs suggested that GIFT may increase the incidence of heterotopic pregnancy because multiple gametes are placed into fallopian tubes that may have microscopic endosalpingeal changes, which could result in multiple fertilization with the potential for both intrauterine and tubal implantation 23 . Interestingly, contralateral pregnancies after GIFT have been reported 24,25 . Ranieri et al 24 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Interestingly, contralateral pregnancies after GIFT have been reported. 24,25 Ranieri et al . 24 concluded that the risk of ectopic pregnancy after assisted conception can be present even when the fallopian tubes are apparently normal.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of ectopic pregnancy has increased during the last decades. This might be explained by an increased number of pelvic inflammatory diseases especially chlamydia trachomatis infections (7). Additionally the prevailing use of intrauterine devices and the increased number of microsurgical repairs of occluded Fallopian tubes has raised the risk of ectopic pregnancy (7).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing an ectopic pregnancy in heterotopic pregnancy by hCG analysis is impossible since the intrauterine pregnancy will produce normal amounts of hCG. Serial sonographic examinations have not improved the diagnostic accuracy (7). In fact, a preoperative diagnosis of heterotopic pregnancy was present in only 10% of cases (6) and despite improved diagnostic safety the majority of ectopic pregnancies in heterotopic pregnancy will be diagnosed because of bleeding from the ectopic pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation